Seventy years of sex education in Health Education Journal: a critical review. (January 2015) - Iyer, Padmini; Aggleton, Peter
This paper examines key debates and perspectives on sex education in Health Education Journal ( HEJ ), from the date of the journal's first publication in March 1943 to the present day. Matters relating to sexuality and sexual health are revealed to be integral to HEJ 's history. First published as Health and Empire (1921 – 1942), a key purpose of the journal since its inception has been to share information on venereal disease and its prevention within the UK and across the former British Empire. From 1943 to the present day, discussions on sex education in the newly-christened HEJ both reflect and respond to evolving socio-cultural attitudes towards sexuality in the UK. Changing definitions of sex education across the decades are examined, from the prevention of venereal disease and moral decline in war-time Britain in the 1940s, to a range of responses to sexual liberation in the 1960s and 1970s; from a focus on preventing sexually-transmitted infections, teenage pregnancy and HIV in the 1980s, to the provision of sexual health services alongside sex education in the 2000s. Over the past 70 years, a shift from prevention of pre-marital sexual activity to the management of its outcomes is apparent; however, while these changes over time are notable, perhaps the most striking findings of this review are the continuities in arguments for and against the discussion of sexual issues. After more than 70 years of debate, it would seem that there is little consensus concerning motivations for and the content of sex education.